Rhizobacterium‐derived diacetyl modulates plant immunity in a phosphate‐dependent manner. (5th December 2019) - Morcillo, Rafael JL; Singh, Sunil K; He, Danxia; An, Guo; Vílchez, Juan I; Tang, Kai; Yuan, Fengtong; Sun, Yazhou; Shao, Chuyang; Zhang, Song; Yang, Yu; Liu, Xiaomin; et al.
Abstract: Plants establish mutualistic associations with beneficial microbes while deploying the immune system to defend against pathogenic ones. Little is known about the interplay between mutualism and immunity and the mediator molecules enabling such crosstalk. Here, we show that plants respond differentially to a volatile bacterial compound through integral modulation of the immune system and the phosphate‐starvation response (PSR) system, resulting in either mutualism or immunity. We found that exposure of Arabidopsis thaliana to a known plant growth‐promoting rhizobacterium can unexpectedly have either beneficial or deleterious effects to plants. The beneficial‐to‐deleterious transition is dependent on availability of phosphate to the plants and is mediated by diacetyl, a bacterial volatile compound. Under phosphate‐sufficient conditions, diacetyl partially suppresses plant production of reactive oxygen species (ROS) and enhances symbiont colonization without compromising disease resistance. Under phosphate‐deficient conditions, diacetyl enhances phytohormone‐mediated immunity and consequently causes plant hyper‐sensitivity to phosphate deficiency. Therefore, diacetyl affects the type of relation between plant hosts and certain rhizobacteria in a way that depends on the plant's phosphate‐starvation response system and phytohormone‐mediated immunity. Synopsis: A volatile compound produced by a plant growth‐promoting rhizobacterium differentially affects phytohormone‐mediated immunity in phosphate‐sufficient and ‐deficient plants, thus modulating their response to symbiont colonization. Exposure to a plant growth‐promoting rhizobacterium Bacillus amyloliquefaciens can cause either beneficial or deleterious effects on Arabidopsis thaliana plants depending on their nutrition status. The beneficial vs. deleterious effects of the rhizobacterium depend on the availability of phosphate (Pi) to the plant. The effect of the rhizobacterium on plant fitness is mediated by the volatile bacterial metabolite diacetyl (DA). In Pi‐sufficient plants, DA partially suppresses plant immune response and enhances symbiont colonization without compromising disease resistance. In Pi‐deficient plants, DA enhances phytohormone‐mediated immune response and causes plant hypersensitivity to Pi deficiency. Abstract : A volatile compound produced by a plant growth‐promoting rhizobacterium differentially affects plant immunity and plant response to symbiont colonization depending on phosphate availability.